Databases DeMYSTiFieD, 2nd Edition, 2nd Edition - Oppel, Andrew J. (McGraw-Hill, 2010)
Learning DATABASE fundamentals just got a whole lot EASIER! Now you can design, build, and manage a fully functional database with ease. Thoroughly updated to cover the latest technologies and techniques, Databases Demystified, Second Edition gives you the hands-on help you need to get started. Written in a step-by-step format, this practical guide covers methods that can be used with any database, including Microsoft Access, MySQL, Microsoft SQL Server, and Oracle. You'll learn about relational database components, database queries, SQL, the database life cycle, logical database design using normalization, and physical database design. Data and process modeling, database security, Online Analytical Processing (OLAP), and XML are also covered. Detailed examples and concise explanations make it easy to understand the material, and end-of-chapter quizzes and a final exam help reinforce learning. It's a no-brainer! You'll find out how to: Create and run database queries using the forms-based query tool in Microsoft Access Write SQL statements and queries Use entity relationship diagrams (ERDs) for data modeling Design physical tables Connect databases to users, computer systems, and applications Secure database data Handle cursor processing, transaction management, and performance tuning Integrate XML documents and objects into databases Simple enough for a beginner, but challenging enough for an advanced student, Databases Demystified, Second Edition is your self-paced guide to learning universal database concepts.